Measurement and Simulation of Indoor Thermal Environment of Residential Building in Chengdu of China - Ouyang, Jinlong; Mo, Wenshen; Zhao, Lingxi; Iamtrakul, Pawinee (International Journal of Building, Urban, Interior and Landscape Technology, 2018)
To better understand the current situation of indoor thermal environment of residential buildings in Chengdu of China, a house located in one typical residential building which met the thermal insulation requirements of the 50% energy-efficient design standard was selected as the research object. Then its indoor thermal environment was measured and the information about occupants’ lifestyle was collected both in summer and in winter. The field-measured results showed the indoor thermal environment was poor. The mean indoor temperature in summer reached approximately 34.0 °C, while that in winter was only about 11.0°C and the relative humidity was often higher than 70%. Meanwhile, based on the information obtained from the survey, the indoor thermal environment of the case house was simulated by using DeST-h. The simulation results showed that the change trends of the simulated temperatures in the rooms of the case house in the typical days were close to those of the measured results. Finally, one conclusion could be drawn that the thermal insulation of envelope enclosure could not ensure a comfortable indoor thermal environment. Further, it revealed that perhaps such measures might not be good energy-efficient measures for the residential buildings in Chengdu.